DEVELOPMENT OF ECO-CULTURE TO IMPROVE ENVIROMENTAL LITERACY IN ELEMENTARY SCHOOL - Karenina Shashal Agsari; Mayang Kusumaning Rahady; Wahyudi Wahyudi (Universitas Sebelas Maret, 2018)
The objectives of writing scientific papers are: (1) describing eco-culture, (2) describing ecoliteration of the environment, and (3)to describing ways to improve environmental ecoliteracy by means of eco-culture in elementary schools. The method used is literature study, which is data collection techniques by conducting study studies of books, literature, notes, and reports that are related to the problem being solved. Library sources in this study were obtained from: books, journals and research results (thesis, thesis, and dissertation). So that in this study include general processes such as: systematic theory identification, library discovery, and documentary analysis which contains information relating to the research topic. The results of this study are (1) eco-culture a process of increasing understanding, knowledge, attitudes and behavior based on ecology. (2) environmental echoliteration is to teach children to love the environment through greening. (3) improve environmental ecoliteracy in primary schools by take care and practicing directly maintaining and caring for the school environment.